Rationale and protocol for an observational study of in vivo stress experiences and real-time cardiovascular responses among young, black women: The DYNAMIC study - Anika L. Hines; Fota Sall; Shawn Utsey; Robert Perera; Ron K. Evans; Lisa A. Cooper; Jessica Gokee LaRose (PLoS ONE, 2025)
Background Chronic stress is thought to contribute to racial disparities in cardiovascular morbidity and mortality among women. Intervention development has been stalled by complex issues regarding stress measurement as well as the correlation of varying stress experiences with proximal cardiac responses in naturalistic environments. Methods The Designing Young Adult Interventions to Address and Mitigate Inequities in Cardiovascular Health (DYNAMIC) Study is an observational study of the stress experiences of young Black women reported in vivo and within naturalistic context. The study will enroll up to 50 participants aged 18 to 39 years old. Participants will undergo a 14-day protocol, including completion of random surveys regarding stressor administered via ecological momentary assessment (EMA) while wearing a 24-hour ambulatory ECG monitoring patch and actigraph watch to capture a continuous feed of physiological responses. Participants will also measure and log wakening and bedtime blood pressure readings using a validated cuff. Discussion The study addresses ongoing challenges to validity in correlating stress to cardiovascular outcomes. The combination of EMA surveys and continuous physiological monitoring provides rich data regarding stress response, including frequency, duration, and attribution to specific stress stimuli. The primary outcomes of the study are heart rate variability and blood pressure. The secondary outcome of this study is ideal cardiovascular health—an index of measures predicting healthy cardiovascular aging. Conclusion Findings from this study may be used to inform responsive, tailored interventions for young Black women towards the aims of primordial prevention and early intervention to promote cardiovascular health and reduce disparities.